Study of Dexmedetomidine in Caudal Block for Children Undergoing Inguino-scrotal Surgery - Gautam, B.; Piya, B.; Karki, D. (Kathmandu University Medical Journal, 2020)
Background Caudal block is the most common anaesthetic technique employed in children for managing perioperative pain of inguino-scrotal surgery. However, despite using long-acting local anaesthetics, caudal analgesia lasts relatively shorter. Dexmedetomidine, an alpha-2 agonist, augments local anaesthetic action. Objective To assess the analgesic effect of caudal Dexmedetomidine. Method This is a randomized, double-blinded study conducted on otherwise healthy children (one to five years) undergoing elective inguino-scrotal surgery. General anaesthesia was administered and a laryngeal mask airway was inserted for assisting ventilation. The caudal block was applied using 0.8 milliliters/kilogram drug volume comprising either two milligrams/kilogram Bupivacaine in group A (n=42) or two milligrams/ kilogram Bupivacaine mixed with 0.75 micrograms/kilogram Dexmedetomidine in group B (n=42). Intraoperatively, inhaled Halothane, intravenous Fentanyl, fluids, and ventilation were titrated to maintain monitored hemodynamic variables within 15% from baseline values. The primary endpoint comprised the duration of analgesia, defined by a time when postoperative pain score (face, legs, activity, cry, consolability; FLACC scale) reached four out of ten. Perioperative events were studied for 24 hours. Student’s t-test and Chi-square test were used for analysis, with p-value less than 0.05 considered as significant. Result Demographic, surgical, and anaesthetic characteristics were similar between the groups. Duration of analgesia was significantly prolonged in group B (group B, 413±101 minutes; group A, 204±40 minutes). The intraoperative requirement for supplement Fentanyl was significantly reduced in group B. Adverse events were comparable between the groups. Conclusion Dexmedetomidine prolongs the duration of analgesia when mixed with caudal Bupivacaine, without increasing adverse events.